Steep differences in wingless signaling trigger myc-independent competitive cell interactions. - Vincent, J.P.; Kolahgar, G.; Gagliardi, M.; Piddini, E. (Developmental Cell, 2011)
Wnt signaling is a key regulator of development that is often associated with cancer. Wingless, a Drosophila Wnt homolog, has been reported to be a survival factor in wing imaginal discs. However, we found that prospective wing cells survive in the absence of Wingless as long as they are not surrounded by Wingless-responding cells. Moreover, local autonomous overactivation of Wg signaling (as a result of a mutation in APC or axin) leads to the elimination of surrounding normal cells. Therefore, relative differences in Wingless signaling lead to competitive cell interactions. This process does not involve Myc, a well-established cell competition factor. It does, however, require Notum, a conserved secreted feedback inhibitor of Wnt signaling. We suggest that Notum could amplify local differences in Wingless signaling, thus serving as an early trigger of Wg signaling-dependent competition.